Evaluation and comparison of different blood culture techniques for bacteriological isolation of Salmonella typhi and Brucella abortus. - Gaviria-Ruiz, M M (1995)
An experimental study was carried out to evaluate and compare various noncommercial methods of blood culture for the isolation of Salmonella typhi and Brucella abortus from fresh human blood samples that had been artificially inoculated with 1 to 50 microorganisms per ml of blood. The methods compared included the Ruiz-Castañeda blood culture, broth blood culture, leukocyte lysis and direct plating on agar (WBL-P), leukocyte lysis and filtration, Ficoll-Hypaque centrifugation and filtration, Ficoll-Hypaque centrifugation, and Ficoll-Hypaque centrifugation and leukocyte lysis methods. Results with the WBL-P technique showed that S. typhi was isolated in 18 h, and its recovery rate was 36.6% (calculated from the number of CFU recovered per milliliter versus the number inoculated). B. abortus was isolated in 48 h by the same technique, and its recovery rate was 48.8%. The isolation times for the other blood culture techniques were between 36 and 44 h for S. typhi and 66 h for B. abortus. The techniques which relied on filtering systems for the recovery of S. typhi and B. abortus performed poorly. The WBL-P technique for the isolation of S. typhi and B. abortus is faster than the other methods tested.